Perception and Behavior in Prevention of Dengue Hemorrhagic Fever in Ubon Ratchathani Province - Wongbutdee, Jaruwan; Saengnill, Wacharapong; Krasuaythong, Nantaya (Journal of Health Science of Thailand, 2018)
Dengue Hemorrhagic Fever (DHF) is a major health problem in Ubon Ratchathani Province. The epidemic was spurred by lack of a better understanding of local people in DHF surveillance and control. The purposes of the study included the perception of local people in DHF and the behavior of DHF surveillance. Ten villages with high incidence of DHF cases within the last 3 years (2005- 2007) were selected as a study site. Data were collected in March 2008 in an interview of 383 households. The results showed high level of perception of local people in DHF among 91.10 percent of the samples. On behavior of DHF prevention, it was reportedly at a high level (50.90%). The relationship between perceptions of DHF and behavior of DHF surveillance was statistically significant (r = 0.26, p < 0.001). This result was to provide data base for prevention and control of DHF further.